Results of the ribonuclease isolation from the cobra venom by ion-exchange column with CM-cellulose method - Thiet, Nguyen Van; Son, Giang Thai (Academia Journal of Biology, 2014)
In this paper, the cobra (Naja atra Cantor, 1842) venom ribonuclease (RNase) was isolated of ion-exchange column with CM-cellulose method. The chromatographic isolation was carried out at different values of pH within an interval of pH = 4.4 – 5.8. At pH > 5.0, the cobra venom RNase was almost always eluded from the column in two picks at salt concentrations of about 0.6 M and 0.8 M NaCl; but in some cases - in three picks at salt concentrations of about 0.5 M, 0.65 M and 0.86 M NaCl, respectively; whereas, at pH < 5.0, the cobra venom RNase was always eluded from the column in single broad pick. The forms of the cobra venom RNase corresponding to these picks were designated as SK-1, SK-2 and SK-3, respectively. It seemed that these RNase forms were differed from each other in many properties, such as an optimum of pH (pHopt) and the kinetic property. Thus, the pHopt of the form SK-2 was about 2.5, whereas this value of the forms SK-1 and SK-3 was the same and about 2.0. Besides, two main forms SK-2 and SK-3 had sigmoidal curves of the saturation of the enzyme with the substrate, but they differed significantly in an affinity to the substrate.